The effect of Lemna perpusilla Torr. (Araceae) as fodder in the growth of Osphronemus goramy Lacépède, 1801 - Sherly Suryaningsih; Hamiyati; Vania Zulfa (LPPM Universitas Negeri Jakarta, 2024)
Production of gourami as consumption fish is rather lengthy, as it attains commercial size in 1—2 years, longer than other commercial fish. Therefore, fish production is hampered by higher fodder costs. It is a normal practice in gourami rearing, that farmers supplement commercial fodder with naturally available fodder, especially from material such as taro leaves. However, some materials may contain less nutrients, compared to others. It is why we propose the use of Lemna perpusilla, a widely distributed water aroid as gourami fodder supplement. We measured the growth of gourami fries, which are length (cm) and weight (g) and found that fishes with L. perpussila pellet attain higher length and weight compared to those using commercial pellet. This research may be beneficial for freshwater weed management as well as fish production with low capital, i.e. village production.